Education for Sustainable Development: A Study on the Attitude and Concerns on Climate Change Issues among Elementary School Teachers of Odisha, India - Mohapatra, Shashwoti; Mallik, Kapileswar; Satapathy, M. K. (Asian journal of education and social studies, 2022)
From fatal heat waves and cruel droughts to devastating floods and fast depleting water tables, climate change is the greatest destructor in the current time creating a threat to all living organisms including human being. Teachers being the agents of social change have an important role to play in moulding the behaviour of children to cope with the climate change stress. The present study was carried out with 462 (222 pre-service and 240 in-service) elementary school teachers taking a Likert type five point attitude scale with 30 items having six dimensions viz., science of climate change, causes of climate change, impacts of climate change, mitigation, national initiatives and policies and politics of climate change.
From the study, it was noted that though both pre-service and in-service teachers had favourable attitude towards climate change issues, pre-service teachers had higher level of concern than in-service teachers as reflected from their attitude scores. Dimension wise pre-service and in-service teachers had favourable attitude towards science of climate change, causes of climate change, impacts of climate change and mitigation, and negative attitude towards national initiatives and policies and politics of climate change. Urban teachers were more favourable than rural teachers in first four dimensions studied.
However, among in-service teachers rural teachers were more concerned on issues such as impacts of climate change and causes of climate change than on science of climate change, mitigation, national initiatives, policies and politics of climate change. Among pre-service teachers, there was no significant difference in the attitude scores between science and arts teachers, and male and female teachers. However, urban teachers had more favourable attitude than rural teachers. Among in-service teachers, there was significant difference in the attitude scores as far as subject (science/arts) and residence (urban/rural) are concerned. Rural in-service teachers had more favourable attitude than urban teachers.
The correlation between knowledge and attitude showed a positive relationship which reflected that with increase in knowledge there was increase in concern. The relationship between age and attitude showed that with increase in teacher’s age concern for climate change increased.
openalex: W4285095005
Keywords: C:India; _z:class:countries; _z:class:themes; oa:keyword:climate change issues; oa:keyword:sustainable development; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11835 Sustainability Education in Higher Education Institutions; openalex:import; openalex:yes